2021
DOI: 10.1016/j.eclinm.2021.101070
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies and neurological manifestations in acute COVID-19: A single-centre cross-sectional study

Abstract: Background A high prevalence of antiphospholipid antibodies has been reported in case series of patients with neurological manifestations and COVID-19; however, the pathogenicity of antiphospholipid antibodies in COVID-19 neurology remains unclear. Methods This single-centre cross-sectional study included 106 adult patients: 30 hospitalised COVID-neurological cases, 47 non-neurological COVID-hospitalised controls, and 29 COVID-non-hospitalised controls, recruited betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…Antiphospholipid antibodies (i.e., anti-phosphatidylserine/prothrombin) were higher in COVID-19 patients, particularly those with neurological manifestations, than in controls. In contrast, anticardiolipin antibodies were not associated with neurologic involvement in COVID-19 ( 96 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 80%
“…Antiphospholipid antibodies (i.e., anti-phosphatidylserine/prothrombin) were higher in COVID-19 patients, particularly those with neurological manifestations, than in controls. In contrast, anticardiolipin antibodies were not associated with neurologic involvement in COVID-19 ( 96 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 80%
“…Following the fnding of Bahramnezhad et al, which describes a case of an antiphospholipid-like condition caused by COVID-19 [31], another piece of evidence from the literature is the fnding of Moon et al [32], who presented a hypothetical model to elucidate the pathophysiology of APS in COVID-19 and described clinicopathological similarities between CAPS and severe COVID-19 [32]. In light of this evidence and our fndings, COVID-19 may induce an antiphospholipid-like condition that plays a role in increasing the severity of disease manifestation; this hypothesis is strongly supported by the fndings of Laura et al, who examined 106 COVID-19 patients for the presence of aPL antibodies, including 30 hospitalized cases, 47 hospitalized nonneurological COVID-19 controls, and 29 COVID-19 nonhospitalized controls, and reported a high prevalence of antiphospholipid antibodies in 72 (67.9%) of all cases and 22 (73.3%) of the 30 hospitalized neurological cases [33]. An important note in our study is to mention that the positive case of aPL is also positive for the ANCA, indicating that a range of autoantibodies could be induced in COVID-19 infection.…”
Section: Discussionmentioning
confidence: 81%
“…4,5 Among different factors identified, thrombotic complications might be specifically induced by the presence of lupus anticoagulant and other antiphospholipid antibodies or by the development of an autoimmune vasculitis elicited by the virus. 3,5,39 In this regard, primary and secondary causes of isolated retinal vasculitis, including virus-induced vasculitis, have been previously described. 40 Our study showed that retinal vascular occlusions were not accompanied by thrombotic or occlusive lesions in other territories in most of the patients.…”
Section: Discussionmentioning
confidence: 99%